2005
DOI: 10.1080/02724980343000954
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Variation in Performance of an Interceptive Action with Changes in the Temporal Constraints

Abstract: People are highly skilled at intercepting moving objects and are capable of remarkably accurate timing. The timing accuracy required depends upon the period of time for which contact with a moving target is possible--the "time window" for successful interception. Studies of performance in an experimental interception task that allows this time window to be manipulated suggest that people change aspects of their performance (movement time, MT, and movement speed) in response to changes in the time window. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…These results are in line with several other studies reporting changes in the velocity or in the MT of interceptive movements relying on the velocity of the target (e.g. Tresilian and Houseman 2005;Tresilian et al 2003;Brouwer et al 2000Brouwer et al , 2002Brouwer et al , 2003Brenner et al 1998), which determines the temporal precision that the movement requires and the temporal window of the target.…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with several other studies reporting changes in the velocity or in the MT of interceptive movements relying on the velocity of the target (e.g. Tresilian and Houseman 2005;Tresilian et al 2003;Brouwer et al 2000Brouwer et al , 2002Brouwer et al , 2003Brenner et al 1998), which determines the temporal precision that the movement requires and the temporal window of the target.…”
Section: Introductionsupporting
confidence: 90%
“…The possible use of the information from the online changing temporal window has not been considered previously. Tresilian and Houseman (2005) and Tresilian and Plooy (2006) showed that subjects change the way they perform their movements depending on the target's temporal window. Specifically, they reported changes in the MT in relation to the time window: small temporal windows promote shorter MTs, while bigger temporal windows promote longer MTs.…”
Section: Discussionmentioning
confidence: 99%
“…The proposed flexibility in using information at any relevant time means that one must determine when visual information would be useful for any task that one studies. In tasks that require very precise timing of movement onset, seeing the target just before that moment may have a strong influence on performance, so there will in fact be a critical time (Tresilian and Houseman 2005;Lee et al 1983). If the variability in the position of the catch is high one will have to see earlier parts of the trajectory because corrections will take longer.…”
Section: Discussionmentioning
confidence: 99%
“…By constraining the task, one can make people rely on specific kinds of information at particular times. If subjects are required to initiate a pre-programmed movement at a critical moment (Tresilian and Houseman 2005), they will primarily response to visual information that helps them judge that moment. If the conditions make it hard to predict the ball's trajectory, then the prediction will constantly change so that vision remains essential until the very end (Peper et al 1994;Montagne et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known from previous studies that while higher velocity movements promote better temporal accuracy (e.g., Tresilian & Houseman, 2005;Tresilian, Oliver, & Carroll, 2003), lower velocity movements promote better spatial accuracy (e.g., Fitts & Peterson, 1964;Harris & Wolpert, 1998;Meyer et al, 1988;Schmidt, 1988;Schmidt, Zelaznik, Hawkins, Frank, & Quinn, 1979). It has also been shown that people (optimally) combine viewing time and execution-motor time when performing a reaching task under spatial constraints only (e.g., Battaglia & Schrater, 2007).…”
Section: Discussionmentioning
confidence: 99%